Human health risk associated to particulate matter and polycyclic aromatic hydrocarbon levels and their relation with preponderant sources in Gran La Plata, Argentina - Giuliani, Daniela Silvana (2021)
Levels of suspended particulate matter (PM) of both fractions PM₁₀ and PM2.5 in ambient air were monitored in three areas of Gran La Plata: industrial, urban, and residential (2017-2019). Associated polycyclic aromatic hydrocarbons (PAHs) and nitropolycyclic aromatic hydrocarbons (NPAHs) to PM were also determined and possible emission sources were identified. Assessment of health risk to PM exposure and associated compounds was realized. Results showed a decrease in levels of PM₁₀ in each area along the period studied, especially in the industrial area. Decreases in PM2.5 levels were also observed in urban and residential areas over the years, although the trend is not as marked as with PM₁₀ levels. Then, PM2.5 levels in the industrial area have remained practically constant. The 89% of both PM₁₀ and PM2.5 annual mean exceeds the WHO reference values. The presence of most of the 16 US EPA priority PAHs studied was found with a detection frequency greater than 60% and it was possible to identify the importance of the contributions of vehicular emissions as predominant sources of PAH emission. From the calculations of the risk of contracting cancer throughout life (LCR), in the case of adults, the US EPA limits were not complied in the industrial and urban areas and in both fractions of PM. From the evaluation of the burden of disease (EBD), the calculated relative risks of mortality were very similar for the studied districts, being the relative risk in La Plata slightly lower, about 3-5%, than those in Berisso and Ensenada.